2014
DOI: 10.1111/1753-0407.12108
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: Risk evaluation of cancers in Chinese diabetic individuals: a longitudinal (REACTION) study (队列简介:中国糖尿病患者肿瘤发生风险的纵向研究(REACTION研究))

Abstract: The multi-center REACTION study has captured a broad range of data on physical, psychological and metabolic function as well as health status, biochemical and lifestyle information in 259 657 adults from the general population across the China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 24 publications
1
146
0
1
Order By: Relevance
“…Physical activity was estimated by the Global Physical Activity Questionnaire and was measured by the metabolic equivalent 16. Measurements of anthropometry, including weight, standing height and waist circumference, were carried out by trained nurses according to a standard protocol 17. An electronic sphygmomanometer (OMRON Model HEM‐725FUZZY; Omron Company, Dalian, China) was used to measure blood pressure three times consecutively on the non‐dominant arm with a 3‐min interval after a 5‐min rest.…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was estimated by the Global Physical Activity Questionnaire and was measured by the metabolic equivalent 16. Measurements of anthropometry, including weight, standing height and waist circumference, were carried out by trained nurses according to a standard protocol 17. An electronic sphygmomanometer (OMRON Model HEM‐725FUZZY; Omron Company, Dalian, China) was used to measure blood pressure three times consecutively on the non‐dominant arm with a 3‐min interval after a 5‐min rest.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of REACTION study has been described previously 14, 15, 16. Eligible study participants were identified from the local residence registration records and must be age 40 years or older.…”
Section: Methodsmentioning
confidence: 99%
“…This study was one part of the baseline survey from the REACTION study, which was a multicenter, prospective cohort study; its primary objective was to demonstrate whether abnormal glucose metabolism was associated with increased risk of cancer in a Chinese population [5, 6]. The study was approved by the ethics committee of Ruijin Hospital, Shanghai Jiaotong University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%